THE ANALYSIS OF ARTIFICIAL INTELLIGENCE (AI) USAGE PHENOMENA IN ONLINE DISCUSSIONS OF ECONOMIC EDUCATION STUDENTS - Lodya Sesriyani; Sri Rahayu (Universitas Muhammadiyah Metro, 2026)
ABSTRACT The rapid integration of Artificial Intelligence (AI) in the higher education ecosystem poses new challenges to the originality of thought and students' cognitive processes. While AI offers efficiency, its unregulated use has the potential to degrade critical inquiry skills, particularly in courses demanding a profound understanding of human behavior. This study aims to analyze the phenomenon of AI usage among second-semester students in the Economic Education Study Program, specifically within the